2010
DOI: 10.1097/rlu.0b013e3181ea33e5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Paragonimiasis Revealed by FDG PET/CT

Abstract: A 72-year-old asymptomatic man with a hepatic lesion incidentally detected by ultrasonography in routine examination undertook fluorodeoxyglucose (FDG)-positron emission tomography/computed tomography for further evaluation. The images revealed increased FDG activity in the lesion, which was suggestive of malignancy. However, the pathologic examination demonstrated that the lesion was a granuloma caused by Paragonimus westermani, a lung fluke. Although increased FDG activity in the lung due to P. westermani in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Once the liver is infected, it is difficult to distinguish paragonimiasis with HCC. Although FDG PET/CT scans are currently used to diagnose hepatic parasites, FDG activity during malignancy renders them inaccurate [ 14 , 15 ]. Previous studies had demonstrated that the MDCT features of hepatic paragonimiasis were favorable for its specific diagnosis [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the liver is infected, it is difficult to distinguish paragonimiasis with HCC. Although FDG PET/CT scans are currently used to diagnose hepatic parasites, FDG activity during malignancy renders them inaccurate [ 14 , 15 ]. Previous studies had demonstrated that the MDCT features of hepatic paragonimiasis were favorable for its specific diagnosis [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of parasitosis suspected as malignancy in PET have been previously reported but are very rare [ 11 13 ]. There are no reports investigating the mechanisms of FDG uptake in parasitosis granuloma.…”
Section: Case Presentationmentioning
confidence: 99%
“…Paragonimus larvae, starting their migration track in the intestinal wall, may get access to the liver and there produce parasitic mass lesions. These lesions, most of which consist of a marked inflammatory response, are macroscopic and spherical, mimicking malignancy at imaging (Lee et al 1985(Lee et al , 1987Singcharoen et al 1988;Kim et al 1991Kim et al , 2002Kim et al , 2004Nabeshima et al 1991;Takemasa et al 2002;Cheng et al 2010;Li et al 2012). On CT images, the lesions usually present as clusters of small cysts with rim enhancement in peripheral parts of the liver (Kim et al 2004).…”
Section: Liver Involvementmentioning
confidence: 99%